Unbelievable : From My Childhood Dreams to Winning Olympic Gold - Ennis, Jessica, 1986- (London Hodder & Stoughton, 2012)
On 4 August 2012 Jessica Ennis kicked off what some described as the greatest night in British sporting history. For her it was the end of a long, winding, and sometimes harrowing road. Nobody was under more pressure at the London Olympics than 'the face of the Games'. Yet Jessica delivered the heptathlon gold medal, and the huge outpouring of relief she showed afterwards hinted at the roller-coaster journey she had been on. Behind the smiles and politeness, Jessica has endured much. Bullied at school for being small, she proved to critics and rivals alike that size really didn't matter. Hers is an inspiring tale of following your dreams no matter what life throws at you.
Include Index and Illustration
Keywords: Women athletes -- Great Britain -- Olympic Games